Implementasi Kebijakan Sistem Elektronik Surat dalam Mewujudkan Electronic Government di Provinsi Jawa Tengah - Mansyur Achmad; Hamsah Hamsah; Nurkadarwati Nurkadarwati (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2021)
This study aims to identify and describe how the implementation of office administration system policies (E-Mail) in realizing E-Government in Semarang City, Central Java Province. The process of collecting data through literature study, interviews, and observations. The informants of this study were related parties, totaling 10 people, which were considered representative in providing information related to the research data needed. Then this research instrument uses interview guidelines and observation sheets. Furthermore, the data were analyzed with the concept of Miles and Huberman: data reduction, data display, Conclusion drawing / verification. The results showed that the implementation of the office administration system policy (E-Mail) has not been optimal. Among other things, there is no regional regulation at the city level that specifically regulates the office administration system (E-Mail).